2020
DOI: 10.1017/s1041610220003579
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence intervention in older adults to improve adaptation and reduce negative mood

Abstract: Objectives: Emotional intelligence (EI) is a strong predictor of negative mood. Applying emotional skills correctly can help to increase positive emotional states and reduce negative ones. This study aims to implement EI intervention designed to improve clarity, repair EI dimensions and coping strategies, and reduce negative mood in older adults. Design: Participants were randomly assigned to the treatment or control group. Setting: Participants were evaluated individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…The results show how EI, problem-focused coping strategies, and resilience influence emotional and cognitive well-being. This suggests that these variables may be key elements in promoting well-being, as previous studies have shown [ 14 , 18 , 19 ]. The dimensions of emotional clarity and emotional repair intervene in positive affect and negative affect, whereas emotional attention influences negative affect.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The results show how EI, problem-focused coping strategies, and resilience influence emotional and cognitive well-being. This suggests that these variables may be key elements in promoting well-being, as previous studies have shown [ 14 , 18 , 19 ]. The dimensions of emotional clarity and emotional repair intervene in positive affect and negative affect, whereas emotional attention influences negative affect.…”
Section: Discussionsupporting
confidence: 58%
“…EI, problem-focused coping strategies, and resilience are key to adaptation processes [ 4 , 18 , 19 ]. These constructs facilitate appropriate responses in stressful situations, and decrease maladaptive emotional reactions, promoting positive moods and reducing the negative ones [ 4 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a metaanalysis of randomized controlled trials (RCTs) showed that nearly half of the psychosocial/behavioral interventions improved components of wisdom such as emotional regulation, empathy, and compassion with medium-to-large effect sizes (Lee et al, 2020). Intervention programs in healthy older adults have also been found to significantly increase overall "emotional intelligence," which encompasses various wisdom-related skills such as emotion regulation and awareness (Delhom et al, 2020). A recent RCT of a group intervention labeled "Raise Your Resilience" improved not only resilience and perceived stress but also overall wisdom, using SD-WISE in 89 older residents of five senior housing communities (Treichler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There is a severe dearth of trait emotional intelligence (trait EI) studies in the field of gerontology and geriatrics and it is in this specific context that Delhom et al (2020) should be welcomed. This brief commentary discusses key issues arising from Delhom et al's study, but also focuses on generally important themes concerning the role of trait EI in old age.…”
Section: Trait Emotional Intelligence In Old Agementioning
confidence: 99%